KELAYAKAN USAHATANI BAWANG MERAH DI DISTRIK TANAH MIRING - Laurentius Kelvin Setiawan Kelyaum; david oscar simatupang; Maria Maghdalena Diana Widiastuti (Musamus University, 2018)
The objective of this research is to setimate cost, revenue, profit, and the feasibity of redonion farming in Tanah Miring District. The method use primary and secondary data. All the redonion farms (46 famers) in Tanah Miring District become free responden. Data analisis used costanalisis, R/C ratio and BEP (Break Event Point) analisized. The result showed that red onion farmingin Tanah Miring District have the cost Rp. 23.526.255 for 3 (three) month in 0,3 ha. The revenueof red onion farming is Rp. 45.738.745/3 (three) month/0,3 ha, with BEP production volume is672/kg and BEP price production is Rp. 11.888/kg. The R/C ratio is 2,9 means that every Rp. 1capital produce 2,9% profit. The concluetion is red onion farming is feasible to developed.Keyword: cost analisys, red onion, dan feasibility analisys.